Ductile failure of occlusive high strength bolt connections under shear force. (May 2020) - Guo, Xiaonong; Zong, Shaohan; Gao, Shuyu; Zhu, Shaojun; Zhang, Yan
Abstract: Based on experimental and numerical analysis, this paper analyzed the ductile failure of the new occlusive high strength bolt (OHSB) connections under shear force. Firstly, static tensile tests on eight specimens were conducted. All the specimens presented ductile failure with the yielding of the teeth and grooves. It was found that the transmission of force is achieved mainly by the occlusion interaction of the teeth and the grooves. Then, refined finite element (FE) models were established using ABAQUS and verified against the experimental results. The good agreement confirmed that the FE models were able to simulate the mechanical behavior of OHSB connections accurately. Based on the validated models, a parametric analysis was carried out to further investigate the behavior of the OHSB connection. Six crucial influence factors were considered, including the friction coefficient between the teeth and the grooves, the number of grooves, the width and the thickness of the cover plates, the diameter and the pretension of the bolts. The results indicated all the factors but the bolt pretension could improve the shear capacity of the connection. Finally, a simplified formula with acceptable accuracy was developed to estimate the shear bearing capacity of double-shear OHSB connections for ductile failure. Highlights: Ductile failure of eight OHSB connections under shear force was investigated. Number of the teeth and grooves can influence the failure modes. Bolt pretension has little effect on ultimate load of OHSB connections. Formulae to predict the bearing capacity of OHSB connections was proposed.